Reading Muslim Tionghoa Culture by Integrating Indigenous Muslim Culture in Indonesian in the Context of Han Kitab - Nurhayati, Dwi Astuti Wahyu; Munawiroh, Afifatul (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2019)
This paper based on exploratory and library research. There are three research questions in this paper; first, How do you explain the indigenous Muslim culture and Muslim Tionghoa in Indonesia? Second, How to combine Muslim Tionghoa and indigenous Muslim culture in Indonesian? Third, How is the incorporation of Chinese and indigenous Muslim cultures in Indonesian affected in the context of Han Kitab? With phemenology approach, researcher analyzed how incorporation of Muslim Tionghoa and indigenous Muslim cultures in Indonesia affected in the context of Han Kitab. Then, the researcher explains the indigenous Muslim culture and Muslim Tionghoa in Indonesia by content analysis.